IMPLEMENTATION OF INNOVATION-BASED CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAM at PT. PERTAMINA REFINERY UNIT (RU) II SEI. PAKNING IN FOSTERING THE ENTREPRENEURIAL SPIRIT OF MIKRO, SMALL,and MEDIUM ENTERPRISES - Mandataris Mandataris; Seno Andri; Ruzikna Ruzikna; Endang Sutrisna; Mashur Fadli (Proceeding of The International Conference on Economics and Business, 2022)
CSR Program of PT. Pertamina RU II Sei Pakning is no longer a charity but is already in the form of a CSR program which is directed to increase people's income through the development ofmicro, small, and medium enterprises. Innovation is not only carried out in the product form of the program, but also innovation in processes, methods, strategies and systems. The goal is that the fosteredmicro, small, and medium enterprisesin the future can exist and be independent. The purpose of this study is to see the extent to which the implementation of the innovation-based CSR program in fostering the entrepreneurial spirit of themicro, small, and medium enterprisescommunity in Sei. Pakning. This type of research uses a mixed method. Methods of data collection is done by means of observation, interviews, questionnaires and documentation. The results showed that the implementation of the innovation-based CSR program at PT. Pertamina RU II Sei. Pakning has not been able to fully cultivate the entrepreneurial spirit of the assistedmicro, small, and medium enterprises. Statistical tests show that there is a significant effect of CSR program innovation consisting of product innovation, process, method, strategy and system on the entrepreneurial spirit of fosteredmicro, small, and medium enterprises. For this reason, it is better for Pertamina RU II Sei. Pakning made improvements to the innovations from the CSR Program they had carried out.